PENGARUH SENSITIVITAS ETIS, GENDER, DAN LOCUS OF CONTROL TERHADAP PERILAKU ETIS MAHASISWA - Midyarany, Desy; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence to the ethically sensitivity, gender differences, and the different of locus of control to the ethically behavior of the accounting students at School of Economics Indonesia (STIESIA) Surabaya. The samples are 80 students of accounting program at STIESIA Surabaya in 2012-2013 periods. The data analysis technique has been done by using simple linear regressions, goodness of fit and t test in the ethically sensitivity, test the ethically behavior different test is based on gender and locus of control which has been done by using independent sample t-test. The result of t test shows that the ethically sensitivity has influence to the ethically behavior of the accounting students, from the result of different of ethically behavior test which has been done by using independent sample t-test, it has been found that there is an influence of the gender different to the ethically behavior of the accounting students, it has been found that the gender different has influence to the ethically behavior of the accounting students and it does not have any influence to the different of locus of control to the ethically behavior of the accounting students.Keywords: Ethics Sensitivity, Gender, Locus of Control, Ethical Behaviour.